INSIDEN PEREDARAN AYAM TIREN PADA PASAR TRADISIONAL DI SURABAYA - Sheila Marty Yanestria; Freshinta Jellia Wibisono (JURNAL KAJIAN VETERINER, 2019)
The aimed of this research was to know the incidence of carrion chicken sales in Surabaya traditional markets. The samples used in this study were chicken meats that had physical characteristics resembling carrion chicken. Chicken meat samples were taken from 20 traditional markets in Surabaya consisting of 5 traditional markets in North Surabaya, 5 traditional markets in East Surabaya, 5 traditional markets in south Surabaya, and 5 traditional markets in West Surabaya. Each traditional market had taken 10 samples of chicken meat each weighing 100 grams coming from different seller. The methode of carrion chicken test that used in this reseach was Malachyte Green Test by Warris method. The results showed that there were no positive sample of carrion chicken in North Surabaya, 9 positive samples of carrion chicken in West Surabaya, 24 positive samples of carrion chicken in South Surabaya, and 14 positive samples of carrion chicken in East Surabaya. The incidence of carrion chicken sales in Surabaya traditional markets showed that there were 47 positive carrion chickens or 23.5% of 200 samples taken.